20 Sowjetische Photographen 1917-1940. - Chudakov, Grigory (Amsterdam : Fiolet & Draaijer Interphoto v.o.f., 1990)
Alpert, Max ; Bulla, Viktor ; Debabov, Dmitrij ; Halip, Jakob ; Ignatovic, Olga ; Ignatovich, Boris ; Langman, Eleazar ; Nappelbaum, Mihail ; Ocup, Piotr ; Petrov, Nikolaj ; Petrussov, Georgii ; Rodchenko, Alexander ; Sagin, Ivan ; Sajchet, Arkadij ; Siskin, Arkadij ; Skurichin, Anatolij ; Steinberg, Jakob ; Sterenberg, Abram ; Zelma, Georgij ; Zukov, Pavel
Biog.
Duits & Engels & Frans & Nederlands
boek
Keywords: Sovjet-Unie